The effectiveness of supportive and psychoeducational family therapy: A linkage towards burden and anxiety of care for children with mental retardation - Isti Harkomah; Nofrida Saswati (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2021)
Background: Children with mental retardation have difficulty processing information so that which affects the development process. Behavioral disorders and dependence on family members with mental retardation lead to care and family responsibilities causing burdens and anxiety in response to stress in mentally disabled children.Purpose: To determine the effectiveness of supportive and psychoeducational family therapy: A linkage towards burden and anxiety of care for children with mental retardationMethod: A quasi-experimental pre-post test design with a control group. The population was the family who has a child with a mental retardation member. The sample was 76 participants using a simple random sampling technique. Data analyzed using Univariate and bivariate.Results: The family burden of mentally retarded children before intervention in the treatment group was 50.18 with a standard deviation of 18.958. The burden on families with mentally retarded children after being given intervention in the treatment group was 46.45 with a standard deviation of 17.168. There are differences in the reduction of burden and family anxiety with mentally retarded children before and after the intervention in the treatment group.Conclusion: Psychoeduactive and Supportive Therapy can be a standard therapy in overcoming the burden and family anxiety in dealing with children with mental retardation. The schools with disabilities need to have a special room to carry out therapy and improve the quality of comprehensive nursing care by recruiting nurses who are competent in providing mental therapy specialists.